Parental attitudes and perceptions associated with childhood vaccine exemptions in high-exemption schools. - Heidi L Pottinger; Elizabeth T Jacobs; Steven D Haenchen; Kacey C Ernst (PLoS ONE)
Previous work demonstrates that individuals who obtain exemptions from school immunization requirements are geographically clustered, making regional differences in vaccination coverage a significant concern. Even where exemption levels are high, there are still parents that vaccinate. School-level assessments have determined that exemptors are more likely to attend wealthier schools with fewer minorities. Few studies have assessed divergent opinions within the context of a higher-exemption community to examine subtle differences in opinion surrounding vaccinations. Therefore, the objective of this work was to assess attitudes and perceptions towards vaccinations and compare them for exemptors and non-exemptors. We administered surveys to parents in high-exemption (>10%) elementary schools in Arizona during the 2012-13 school year. A total of 404 surveys were completed by parents among schools in Maricopa (n = 7) and Yavapai (n = 2) counties. Of these, 35% (n = 141) were exemptors and 65% (n = 261) were non-exemptors. Exemptors were more likely than non-exemptors to be concerned about serious side-effects (p<0.001). They were more likely to report knowing someone who had been diagnosed with a vaccine-preventable disease (p<0.001) but less likely to report that this had been a serious illness in that person (p<0.001) and they believed it is better for a child to develop immunity through illness than vaccination (p<0.001). They were less likely to trust physicians (p<0.001) and information about vaccines (p<0.001) and were more likely to obtain their health care from a naturopath (p<0.001). In summary, exemptors in these Arizona schools do not appear to be exempting their children from vaccinations due to convenience, as has been hypothesized in other settings. Based on the divergent views within high-exemption schools and reported distrust of the medical establishment, target interventions for high-exemption schools are discussed. Additionally, given the lack of effective non-policy based interventions to-date, the negligible declines in personal belief exemption rates, and vaccine preventable disease rate increases in Arizona, especially in high-exemption areas, legislative action in Arizona may also warrant further investigation.